Handcuffed for 15 min: public perceptions of restraint and seclusion in schools: an experimental study of race and disability - Templeton, Da'Shay; Korchagin, Ruslan (Frontiers in Psychology, 2026)
IntroductionThis study examines how members of the U.S. public evaluate the use of restraint and seclusion in schools when the student’s disability and racial identities vary. Restraint and seclusion are legally designated as emergency safety interventions; yet, they are disproportionately used on disabled students, particularly those who are also racially marginalized. Drawing on Disability Critical Race Theory (DisCrit), this study frames these practices as situated at the intersection of racism and ableism.MethodsMethodologically, the study adopts a QuantCrit approach through a randomized online survey experiment with six experimental conditions that varied the students’ race (White, Black, or American Indian) and disability status (disabled or non-disabled). Participants rated school personnel performance, whether the student deserved punishment, whether the punishment fit the behavior, and whether the incident was prejudiced.ResultsResults indicate that disability status, rather than race, significantly shaped participants’ evaluations. Across scenarios, non-disabled students were more likely to be viewed as deserving of punishment and as having received punishment that fit the behavior. Participants also showed slightly higher perceptions of prejudice when the student was Black than when the student was White.DiscussionThese findings suggest a need to further examine how disability is interpreted in public judgments of school discipline and to pursue policy reforms that reduce reliance on restraint and seclusion.